Resting salivary and plasma cortisol in elite athletes following long-haul travel from Australia to Canada - Bullock, N.; Cox, A. J.; Martin, D. T.; Marino, F. E. (Journal of Science and Medicine in Sport, 2009)
Salivary cortisol maybe a preferred method for monitoring the disruption of the body clock following travel across multiple time-zones due to ease of collection and the ability of salivary cortisol to reflect free cortisol. Salivary cortisol concentrations are 5% of plasma cortisol concentrations. Whether the ratio of salivary to plasma cortisol is influenced by travel across time-zones in athletes is not well known. Early morning (8 a.m.) resting salivary and plasma cortisol were measured in five Australian skeleton athletes (4F; 1M) on six mornings over 11 days following international travel from Australia to Canada (eight time-zones). The purpose of this study was to establish whether international travel affected both plasma and salivary cortisol by the same magnitude and for the same duration in this unique athletic population. Plasma cortisol was suppressed on Day-1 and Day-2 (58% and 67% of baseline, respectively), but average values were similar to baseline by Day-4. Salivary cortisol was noticeably suppressed on Day-1 and slightly suppressed on Day-2 and Day-4 but similar to baseline by Day-7. Saliva cortisol tended to be 4% of plasma cortisol at baseline but decreased to 2% on Day-2 and 3.5% on Day-2 and Day-4. These findings document that the relationship between salivary and plasma cortisol can change following international travel and suggest that the extent of the disturbance in cortisol concentrations after crossing multiple time-zones may differ between plasma and saliva samples.